Seabirds in the North-East Atlantic Climate Change Vulnerability and Potential Conservation Actions - Häkkinen, Henry (Open Book Publishers, 2023)
This book was produced by the Zoological Society of London and the University of Cambridge with two aims: to assess seabirds' vulnerability to climate change in the North-East Atlantic, and to identify potential conservation actions that could reduce this vulnerability. 'Seabirds in the North-East Atlantic' collates information from the scientific literature, non-governmental organisations' reports, conservation practitioner input and online databases into a single volume, and provides a reference manual to assist conservation planning. It is intended to be used by anyone who wishes to identify climate change threats to seabirds; to compare threats between different areas of the North-East Atlantic; to start a quantitative climate change vulnerability assessment for a local population; or to review options for conservation action in response to climate change. This book stems from research published in December 2022, but assessments may be updated based on feedback and newly available information. To check for updates to our assessments, please visit our website at: www.ZSL.org/seabird-guidelines.